Design and Simulation for the Multiple-disc Magneto-rheological Fluid Transmission Device - Ren Yankun; Zhang Qiuxiang; Wang Dongdong; Liu Xinhua (Jixie chuandong)
The working principle of magneto-rheological fluids transmission device（MRFTD） is introduced,and the mechanical structure and heat radiation system are designed based on the magneto-rheological Bingham model.The magnetic circuit design and magnetic field simulation are carried out based on finite element analysis software Ansoft Maxwell,thus,the distributions cloud picture of magnetic field under different excitation currents are obtained.The research results that the references and basis for the optimal design of MRFTD are provided.